Kontribusi Father’s Involvement terhadap Perilaku Adolescent Delinquency pada Siswa SMK di Lubuk Basung - Putri, Elvita; Fikry, Zulian (YASIN, 2025)
Adolescent delinquency is a serious issue in the field of education that requires targeted intervention. Multiple factors contribute to this behavior, and the school’s role alone is insufficient to address it effectively. One critical yet often overlooked factor is father’s involvement in parenting. Considering that paternal and maternal parenting styles tend to differ, active paternal involvement becomes a crucial aspect warranting further examination. This study aims to analyze the contribution of father’s involvement, comprising three dimensions: nurturant fathering, reported fathering involvement, and desired fathering involvement, to adolescent delinquency among vocational high school (SMK) students in Lubuk Basung. A quantitative approach was employed, using quota sampling to select 200 students from four SMKs in the region. The instruments included the Nurturant Fathering Scale and the Fathering Involvement Scale to assess paternal involvement, as well as the Adolescent Delinquency Scale to measure levels of delinquent behavior. The results of the analysis indicate that the three dimensions of paternal involvement collectively contribute 28% to adolescent delinquency. These findings underscore the significance of father involvement in parenting as a preventive measure against deviant behavior among adolescents in school settings.